MODEL EKONOMI SUFI: STUDI ATAS BUDAYA EKONOMI TAREKAT SHIDDIQIYYAH - Ahmad Syakur (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Tarekat and Sufism are often used as scapegoats for the Islam declining issue. The concepts of zuhud, fakir, and tawakal are considered to alienate the activities of tarekat from worldly life, so that life is a way of fatalist life and away from the world. This fatalistic teaching adopted by Sufism is considered as the prior cause of cultural poverty among Muslims. The followers of tarekat and Sufism are identified with poverty and slum life. However, it is different from the Tarekat Shiddiqiyah in Jombang Regency which is engaged in business and many members do business and become entrepreneurs. This research is literature research using qualitative descriptive method. The primary data source of this study is murshid’s writings of the tarekat Shiddiqiyah, published books of the tarekat and the official page of the Shiddiqiyah. The focus of this research is: 1). how is the economic culture of the tarekat Shiddiqiyyah and 2). What is the economic framework of the Sufi perspective of the tarekat Shiddiqiyyah. The location of this study is in the tarekat Shiddiqiyah Jombang in East Java. The results of this study are: 1) The fundamental of the tarekat Shiddiqiyyah economic culture is as follows: understanding of zuhud which does not have to stay away from the worldly life , Religion cannot be separated from humanitarian activities, business obligations, disgrace of lazy people and begging, suggestions for helping another human beings and business activities are Jihad fi sabilillah. 2). Shiddiqiyyah's economic activities include business activities and social activities in the form of charity and community economic empowerment. 3). The Sufi economic framework of the tarekat Shiddiqiyyah perspective is: 1). Tawhid is the basis and purpose of economic activity, which includes tauhid al-mashdar and tauhid al-ghayah. 2). Sharia as an instrument of economic activity; and 3). Zuhud as a spirit of economic activity. Zuhud will lead to economic independence, and the charity. Charity in Sufi view will lead to a blessed economy.